WORLD TRADE ORGANIZATION AND THE DEVELOPING WORLDNIGERIAN ECONOMY: A CASE STUDY - Nnabuihe, Nwachukwu Sunny; Odunze, Nwachukwu Tobechukwu; Okebugwu, Nwosu Ezekwesiri (European Scientific Journal, ESJ, 2014)
This research study seeks specifically to ascertain the implications and effects of W. T. O. trade policies on the development of Nigeria economies. It will seek to answer the following pertinent questions: How has Nigerian external trade fared since she became a signatory to the W. T. O. in 1995? How has the adherence to the provisions of the organization affected non-oil exports in Nigeria? How has trade liberalization affected imports into Nigeria? What are the sectoral effects of such imports? Which particular industries are most affected by this liberal import regime? What is the direction of such effects? This research study would be useful in various ways. It will further draw the attention of the government, managers of the economy as well as the general public to the problems associated with the full liberalization of trade. It will also assist policy makers in the choice of policy options as it relates to trade, as issues raised in this study will serve as guide. It will further enhance the available literatures on the trade dynamics between developed and developing countries or between centre states and peripheral states. Finally, it is our hope that the findings of the study will stimulate further researches in this field which will further expand the understanding of the position of third world economies in the global trade system.